PENEGAKAN HUKUM LINGKUNGAN DI INDONESIA - Nurs-Al Umar, Santoso Budi (Universitas Slamet Riyadi, 2011)
AbstractsEnforcement of Environmental Law in Indonesia is still very poor although some times the legal framework related to environmental management are experiencing recent changes made ​​Act number 32 of 2009 on the Protection and Environmental Management. Environmental law enforcement problems occurred in addition to human resource issues are also global environmental problem that is both attractive differing interests between developed and developing countries, because environmental issues are not only related to criminal cases but also civil law. Perhaps the administrative problems to environmental problems must be resolved in a comprehensive and integral. Key words :Enforcement of Environmental Law, the legal aspects related